PROFILING GRADE STUDENTS’ SCIENCE PROCESS SKILLS IN LEARNING INHERITANCE OF TRAITS - Nikmah Alfiatun; Endah Rita Sulistya Dewi; M. Syaipul Hayat (BIOMA : Jurnal Ilmiah Biologi, 2026)
This study aims to investigate and comprehensively describe the profile of Science Process Skills (SPS) among grade XII students in the biology material on Inheritance of Traits at SMA Negeri 1 Ngawen. The study uses a quantitative approach, employing the Research and Development (R&D) method and adapting the ADDIE development model. Quantitative data collection was carried out through tests using SPS assessment instruments in the form of structured essay questions that include 6 main indicators: observing, classifying, predicting, measuring and using numbers, concluding, and communicating. The results of data analysis show a very uneven distribution of students' SPS abilities: only 1.47% of students are included in the "good" category, 19.12% are categorized as "sufficient", 20.59% are categorized as "less", and the absolute majority of 58.82% are in the "very less" category. Cumulatively, the average student KPS score was 41.67% (very poor). This finding underscores the need for a radical reconstruction of biology learning strategies by shifting toward a scientific approach integrated with the STEAM framework to boost students' scientific investigation skills.